LUXURY TOURISM: A PERSPECTIVE OF FACILITIES AND AMENITIES - Ni Made Rai Sukmawati; Ni Made Ernawati; Nyoman Mastiani Nadra (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2018)
The purpose of this study is to conduct a discussion on facilities and amenities of luxury tourism. It is a qualitative study exploring the opinions of travelers on luxury tourism. The study participants consist of 48 respondents who are members of 7 different Facebook travel groups. Data collection was carried out by posting a topic of discussion on luxury travels to the Facebook groups. The results indicate that the conventional way of understanding luxury tourism is highlighted by top class facilities and amenities. These include 5 star and above standard of accommodation, chartered flight, private jet and yacht, butler and limousine service, and spectacular structures. However, contemporarily, luxurious travel is defined more broadly, it does not always connote, e.g. marble bath tub with gold plated tap, it could mean anything comfortable or ease. Luxurious facilities and amenities in tourism are defined differently by different market segments either first, middle or lower class. Thus, there is always a luxurious element for any travel regardless of its class, e.g. a private toilet in the Himalaya is considered as a luxury; there is a luxury for shoestring travelers. It is expected that the analysis could widen the perspective and enrich the discussion on luxury tourism.